Congenital biliary dilatation associated with intestinal malrotation - Takeshi Shirai; Yoshinori Hamada; Hiroshi Hamada; Tatsuma Sakaguchi; Takashi Doi; Mitsugu Sekimoto (Elsevier, 2020)
Congenital biliary dilatation (CBD) associated with intestinal malrotation (IM) has rarely been reported. We herein report three cases of pediatric CBD associated with IM that was incidentally found at surgery. The patients underwent total resection of the extrahepatic bile duct followed by hepaticoduodenostomy at the hepatic hilum or hepaticoduodenostomy as the definitive surgery for CBD. Ladd's procedure was simultaneously performed for asymptomatic IM. Postoperative adhesive intestinal obstruction occurred in all three patients, and conservative treatment was successful. Duodenogastric regurgitation was also observed as a biliary reconstruction-related complication, and conversion to hepaticojejunostomy at the hepatic hilum was performed in two of the three patients. We herein present the clinical course of these three patients and discuss the clinical significance of the association between CBD and IM in terms of the surgical strategy and in comparison with 12 previously reported cases. Keywords: Congenital biliary dilatation, Intestinal malrotation, Postoperative adhesive intestinal obstruction